تحليل كتاب تعليم اللغة العربية لغير الناطقين بها: دراسة لكتاب العربية للحياة وفقًا لنظرية الغالي وحميد: Analisis Buku Ajar Bahasa Arab untuk Pelajar Non-Arab: Analisis Buku Ajar Bahasa Arab dalam Kitab Al-Arabiyyah Lil Hayah Menurut Al-Ghali Dan Hamid - Ibad, Irsyadul; Nidhom, Moch.; Al Farabi, Moh Rifqi Falah (Program Studi Pendidikan Bahasa Arab, Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2025)
This study aims to analyze how the Arabic textbook Al-Arabiyyah Lil Hayah can be a medium in the process of acquiring Arabic for UIN Maulana Malik Ibrahim Malang students and its suitability for non-Arab students according to the theory of Nasir Abdullah Al-Ghali and Abdul Hamid Abdullah. This research is qualitative research with content analysis type. The subject of this study is the Al-Arabiyyah Lil Hayah textbook used by UIN Malang as the main guidebook in the Arabic Language Skill Development Program (PKPBA), which must be followed by all students in the first year of the lecture period. The data collection technique uses documentation by using documentation guidelines to get accurate results. Data analysis uses content analysis according to Krippendorf's theory which consists of the process of unitizing (determining the unit of analysis), sampling (sample selection), coding (coding), reducing (data reduction), abducing (inference taking), and narrating (reporting). The results of this study are (1) the presentation of teaching materials in the ALH book always begins with interactive conversations, the provision of mufrodat with color pictures, Arabic grammatical exercises, question exercises, text analysis, and writing exercises. (2) The ALH book strongly supports the process of acquiring the Arabic language because it always emphasizes the 3M principles, namely; easy, fun, familiar. (3) the preparation of ALH textbooks is in accordance with the standards for the preparation of Arabic textbooks according to the theories of Nasir Abdullah Al-Ghali and Abdul Hamid Abdullah because it always emphasizes the concept of contemporaneity and modernity, so that students can easily learn Arabic with ALH media.